Socio-economic challenges of Ukraine in the war and post-war period - Khatser, Maxim (Management and Entrepreneurship: Trends of Development, 2022)
The article is devoted to the formation of new scientific solutions regarding the identification of crucial socio-economic challenges for Ukraine in the war and post-war period. It has been proven that Russian military aggression and terrorist attacks against the civilian population of Ukraine by the Russian army generate new, primarily negative, challenges to the country's socio-economic system, which will also impact the system in the post-war period. The article aims to identify and characterize the challenges to the Ukrainian socio-economic system at the macro, meso, and micro levels in the war and post-war period, as well as to develop recommendations for eliminating or reducing the impact of negative challenges on the country's economy and social sphere. Methodology: a set of general and special methods has been used at the empirical and theoretical levels, such as the abstraction method for selecting the assessment levels; methods of analysis and synthesis to identify key socio-economic challenges for Ukraine in the war and post-war period; comparison to determine the negative impact of socio-economic challenges and develop recommendations for its elimination at the macro-, meso-, and micro-levels in the country; methods of systematization, grouping and logical generalization for information systematization, development of conclusions and scientific proposals of the article. The study uses the system and functional, historical and systemic approaches to reveal and solve the problems of identifying Ukrainian socio-economic challenges in the war and post-war period. Results: the critical socio-economic challenges of Ukraine in the war and post-war period have been identified, as well as their negative impact on the country's economy and social sphere at the macro-, meso-, and micro levels, and a set of recommendations has been formed to reduce or eliminate the negative impact of the identified challenges.JEL Classification: H10, Н56.